Valuation of goods and services derived from plantation forest in peat swamp forest area: the case of South Sumatra Province. (August 2019) - Ulya, N A; Nurlia, A; Kunarso, A; Martin, E; Waluyo, E A
Abstract: Natural forest area is decreasing but planted forest is increasing by years. The main target of establishment of industrial plantation forest is rehabilitating unproductive production forest areas (mitigate land degradation). Plantation forest ecosystem also expected provide some goods and services even though timber production usually become the main service. This paper aims to present data and information about the value of goods and services derived from plantations forest with case studies in the South Sumatra Province. The Total Economic Value (TEV) concept used as the framework to quantify value of the goods and services derived from plantations forest. The TEV concept widely use to measure the utilitarian value of ecosystems to support efficient resources allocation. The result indicates that the economic value of goods and services derived from plantaton forest that reflected by the TEV of plantation forest is about 17, 242.72 USD. This value is higher than TEV of natural secondary forest and abandoned peatswamp forest. Its indicates that plantation forest can provide both timber and non-timber benefits that generated by the ecological functions of plantation forest. In peat swamps area, development of plantation forest with adaptive species will support timber producion and mitigate forest land degradation.